Design and Production of a Turbojet Engine for Varied Applications - Dzormeku, E.C. (University of Ghana, 2020)
It is acknowledged that turbojets were built with the traditional objective to run aerospace machines. A Turbojet Engine is an air-breathing engine. It produces thrust by ejecting highenergy gas stream from the engine exhaust nozzle. For a while now, Turbojet Engines do not only see operation in the air; they have also become highly essential on the ground. They are mostly used in generating electrical power in the Oil Fields, Mining Sectors and the Heavy Manufacturing Industries. Some Agricultural Industries employ the high heat energy generated from the nozzle of a Turbojet Engine as heat source for drying purposes. Software tools for designing and fabricating machines were some of the major tools used in this project for the construction of the Turbojet Engine. The built Turbojet Engine generated a maximum Thrust of 3.5N, at 100000 Revolution Per Minute (RPM) at a Temperature of 780OC.
MPhil. Nuclear Technology Applications in Petroleum and Mining Industries
Keywords: Turbo Engine; High- energy gas stream; Oil fields; Heavy manufacturing industries